Identification and Validation of Key Genes Associated With Systemic Sclerosis-Related Pulmonary Hypertension - Zheng, Ji-Na; Li, Yang; Yan, Yue-Mei; Shi, Hui; Zou, Tian-Tian; Shao, Wen-Qi; Wang, Qiang (Frontiers in Genetics, 2020)
Systemic sclerosis-associated with pulmonary arterial hypertension (SSc-PAH) is still a major cause of SSc related deaths. Early diagnosis and prompt treatment are crucial to reduce the mortality of patients with SSc-PAH. To screen the candidate biomarkers and potential therapeutic targets for SSc-PAH, we analyzed the data set (GSE33463 and GSE19617) for confirming key genes in peripheral blood mononuclear cells from SSc-PAH patients. A total of 105 SSc patients from gene expression omnibus (GEO) were included as discovery cohort (n=69) and duplication cohort (n=36) for screening hub genes by weighted gene co‐expression network analysis (WGCNA). Furthermore, an independent validation cohort (n=40), including healthy controls, SSc and SSc-PAH patients, was used for further validation by quantitative real-time polymerase chain reaction. The results showed that four key genes, including IFIT2, IFIT3, RSAD2, and PARP14, were confirmed as the new potential biomarkers in SSc-PAH. Also, they could be independent risk factors for SSc-PAH. In conclusion, the four key genes can be expected to become the potential therapeutic targets and early biomarkers for accurate therapy and diagnosis of SSc-PAH in the future, which also provides promising insights into the pathogenesis of SSc-PAH at the molecular level.